Regional Dimensions of Energy Poverty in Households of the Masovian Voivodeship in Poland: Genesis, Factors, Self-Assessment - Oskar Szczygieł; Adrianna Wojciechowska; Vitaliy Krupin; Iryna Skorokhod (Energies)
This study addresses methodical and empirical dimensions of energy poverty based on the case study of the Masovian Voivodeship (also referred to as Mazovia) of Poland, focusing on socioeconomic, technical, and infrastructural factors affecting the thermal comfort of households, while taking into account the local contexts. Using both objective and subjective indicators, this study analyses selected conditions and perceptions of household groups defined as “energy poor”. The representative study group surveyed during the research process includes 2000 residents of the Masovian Voivodeship of Poland. The study was conducted utilising the computer-assisted web interview (CAWI) and computer-assisted telephone interview (CATI) methods. Analysis results show significant regional differences: the prevalence of energy poverty varies significantly depending on energy costs, housing conditions, and heating sources. Results indicate that older buildings and single-family houses, especially those still using coal or wood heating, are characterised by the greatest vulnerability to energy poverty, often related to insufficient insulation and outdated heating infrastructure. Conclusions highlight the urgent need to implement targeted policy interventions, advocating for thermal efficiency programmes and support for low-income households to alleviate the wider socioeconomic and health consequences of energy poverty in the region.